Peningkatan Prestasi Belajar Siswa Dengan Menggunakan Model Pembelajaran Cooperative Integrated Reading And Composition (Circ) - Pratiwi Handayani; Kusworo Kusworo (Faculty of training and education, Pamulang university, 2021)
ABSTRACTThis study examines student learning activities by applying the CIRC learning model to improve student learning outcomes. The research study used a quantitative design with a quasi-experimental method. Time Series Design to find the difference in learning achievement before and after the application of the CIRC learning model. The data generated are the results of cognitive learning achievement of students at SMP PGRI 2 CIPUTAT in the 2019/2020 school year. The findings of this study indicate that prior to the application of the CIRC learning model, students' cognitive learning outcomes tended to be low, namely 56.59, which was not the same as the Minimum Completeness Criteria (KKM). After using the CIRC learning model, the student's learning achievement became 80.04 exceeding the set KKM. If seen from the results before and after the CIRC learning model was carried out, there was an increase in cognitive learning achievement of Class VII students in Social Sciences (IPS) subjects with an increase of 80%.Keywords: CIRC; Learning achievement; Social Science. ABSTRAKPenelitian ini mengkaji kegiatan pembelajaran siswa dengan diterapkannya model pembelajaran CIRC untuk meningkatkan hasil belajar siswa. Kajian penelitian menggunakan rancangan kuantitatif dengan metode quasi eksperimen Time Series Design untuk mencari selisih prestasi belajar pra dan pasca penerapan Model pembelajaran CIRC. Data yang dihasilkan yaitu hasil prestasi belajar kognitif siswa SMP PGRI 2 CIPUTAT tahun ajaran 2019/2020. Temuan penelitian ini menunjukan menunjukkan bahwa Sebelum penerapan model pembelajaran CIRC, hasil belajar kognitif siswa cenderung rendah yaitu 56,59 yakni tidak sama dengan Kriteria Ketuntasan Minimum (KKM). Setelah penggunaan model pembelajaran CIRC prestasi belajar siswa menjadi 80,04 melebihi KKM yang ditetapkan. Jika dilihat dari hasil sebelum dan sesudah dilakukan model pembelajaran CIRC bahwa terdapat kenaikan prestasi belajar kognitif siswa Kelas VII dalam mata pelajaran Ilmu Pengetahuan Sosial (IPS) dengan kenaikan 80%.Kata kunci : CIRC; Prestasi Belajar; IPS.